Pelatihan Referensi Mendeley: Langkah Optimalisasi peningkatan Skor SINTA STAKPN Sentani - Kabanga, Lewi; Tasijawa, Riski; Malatuny, Yakob G.; Bu’tu, Dorce; Layan, Santy; Pentury, Jolanty W.; Rumkabu, Seprianti; Kapojos, Shintia M.; Syafaat, Daniel (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2025)
This community service program aims to enhance the competence of academic writers at STAKPN Sentani in using Mendeley reference management software. The training was designed to help lecturers and writers meet current regulations for producing and publishing scientific works. Participants were grouped into novice writers and those with low SINTA scores. Using an On-the-Job Training (OJT) approach, the sessions were held directly in the participants’ workplace. twenty writers from the departments of Christian Religious Education, Church Music, Theology, and Early Childhood Education took part. The program included initial coordination, core training, and outcome evaluation. Results showed that all participants successfully mastered the use of Mendeley, enabling them to improve the quality and quantity of scientific publications and thereby contribute to increasing the overall SINTA score of STAKPN Sentani.Program Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan kompetensi penulis akademik di STAKPN Sentani dalam menggunakan perangkat lunak manajemen referensi Mendeley. Pelatihan ini dirancang untuk membantu dosen dan penulis memenuhi ketentuan terkini dalam penyusunan dan publikasi karya ilmiah. Peserta dibagi menjadi dua kelompok, yaitu penulis pemula dan penulis dengan skor SINTA rendah. Dengan menggunakan pendekatan On-the-Job Training (OJT), sesi pelatihan dilaksanakan langsung di lingkungan kerja peserta. Sebanyak dua puluh penulis yang berasal dari Program Studi Pendidikan Agama Kristen, Musik Gereja, Teologi, dan Pendidikan Anak Usia Dini mengikuti kegiatan ini. Program meliputi tiga tahapan yakni koordinasi awal, pelatihan inti, dan evaluasi hasil. Hasil kegiatan menunjukkan bahwa seluruh peserta berhasil menguasai penggunaan Mendeley, sehingga mampu meningkatkan kualitas dan kuantitas publikasi ilmiah serta berkontribusi pada peningkatan skor SINTA STAKPN Sentani secara keseluruhan.